Analisis Praktik Green Banking Pada Bank Syariah Di Kota Banda Aceh (Studi Pada Bank Muamalat Indonesia Dan Bank Aceh Syariah) - Nursabna, Shetty; Ibrahim, Azharsyah; Evriyenni, Evriyenni (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
Along with the increase in environmental problems, it has pushed banks to carry out transformations in their behavior and activities, which are known as green banking. The concept of green banking is a long-term business strategy that, in addition to aiming at profit, also creates benefits for empowering and preserving the environment in a sustainable manner. This study aims to describe the initiation of green banking practices at Islamic banks in the city of Banda Aceh by identifying the involvement of Bank Muamalat Indonesia and Bank Aceh Syariah in implementing green banking practices and the obstacles encountered in implementing green banking practices and their solutions. This study used a qualitative descriptive approach with a field research method (field approach through direct interviews with employees at Bank Muamalat Indonesia and Bank Aceh Syariah Banda Aceh Branch). Green banking activity indicators used in this study include carbon emissions, green rewards, green building, reuse/recycle/refurbish, paper work or paperless and green investment. The results of the study show that Islamic banks in the city of Banda Aceh, namely Bank Muamalat Indonesia and Bank Aceh Syariah, have carried out green banking practices based on research indicators, namely carbon emissions, green building, reuse/recycle/refurbish and paper work or paperless. The conclusion of this study shows that of the 6 indicators of green banking activities used in this study including carbon emissions, green rewards, green building, reuse/recycle/refurbish, paper work or paperless and green investment, only 4 indicators have been realized by the two banks. (Bank Muamalat Indonesia and Bank Aceh Syariah), the 4 indicators include carbon emissions, green building, reuse/recycle/refurbish and paper work or paperless.